2022
DOI: 10.1016/j.clim.2022.108929
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of toll-like receptors gene polymorphism on outcome of COVID-19 pneumonia: A case-control study

Abstract: Toll-like receptor 3 (TLR3) and TLR7 genes are involved in the host immune response against viral infections including SARS-COV-2. This study aimed to investigate the association between the TLR3(rs3775290) and TLR7(rs179008) polymorphisms with the prognosis and susceptibility to COVID-19 pneumonia accompanying SARS-COV-2 infection. This case-control study included 236 individuals: 136 COVID-19 pneumonia patients and 100 age and sex-matched controls. Two polymorphisms (TLR3 rs3775290 and TLR7 rs179008) were ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 41 publications
2
20
0
2
Order By: Relevance
“…However, a follow-up study could not reproduce these results [ 30 ]. In addition, a TLR3 (rs3775290) polymorphism has been associated with an increased risk of pneumonia in patients with COVID-19 [ 31 ]. Further studies are needed to define the role of TLR3 in SARS-CoV-2 infection and the development of COVID-19.…”
Section: Innate Immune Sensing and Signaling In Response To Sars-cov-2mentioning
confidence: 99%
“…However, a follow-up study could not reproduce these results [ 30 ]. In addition, a TLR3 (rs3775290) polymorphism has been associated with an increased risk of pneumonia in patients with COVID-19 [ 31 ]. Further studies are needed to define the role of TLR3 in SARS-CoV-2 infection and the development of COVID-19.…”
Section: Innate Immune Sensing and Signaling In Response To Sars-cov-2mentioning
confidence: 99%
“… 94 It was demonstrated that the TLR3 rs3775290 and TLR7 rs179008 genotypes were significantly associated with increased risk of COVID‐19 pneumonia but not the disease outcome. 95 They also found that males with TLR3 SNP (T/T polymorphism) were more susceptible to the disease. TLR7 rs179008 genotype has been also associated with lower expression levels and additionally, HCV and HIV infection with alteration in responses.…”
Section: Tlrs Genes Polymorphismsmentioning
confidence: 98%
“…The intron variant in the IFNAR2 gene (rs2236757) and Interferon‐inducible transmembrane ( IFITM ) genes such as IFITM3 rs12252 genotype has been associated with SARS‐COV‐2 infection 94 . It was demonstrated that the TLR3 rs3775290 and TLR7 rs179008 genotypes were significantly associated with increased risk of COVID‐19 pneumonia but not the disease outcome 95 . They also found that males with TLR3 SNP (T/T polymorphism) were more susceptible to the disease.…”
Section: Tlrs Genes Polymorphismsmentioning
confidence: 99%
“…The sequence of primers used in molecular analysis of this study was detailed in table (1). To examine the optimum annealing temperature of primer, the DNA template was amplified with the same primer pair, (Forward) (Reverse), at annealing temperatures of 55, 58, 60, 63 and 65°C.…”
Section: Primer Preparation and Optimizationmentioning
confidence: 99%
“…In December 2019, a novel infectious disease, called COVID-19 pneumonia, emerged in Wuhan City, China, and is spreading globally. Unfortunately, the ultimate fate of the COVID-19 pneumonia outbreak is unknown, as the situation is rapidly evolving [1]. The innate immune system provides the first-line protection against invading organisms and it is potentially important in SARS-CoV-2 infection [2].…”
Section: Introductionmentioning
confidence: 99%